1995
DOI: 10.7164/antibiotics.48.113
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bioactive .DELTA. lactone FD-211 Taxonomy, Isolation and Characterization.

Abstract: During our screening program for natural product drugs effective against multidrug-resistant mammalian cells, we have discovered a new S lactone FD-211 from the fermantation broth of Myceliophthora lutea TF-0409. FD-21 1 had a broad spectrum activity against cultured tumor cell lines, including adriamycin-resistant HL-60 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Compound 4 had molecular formula C 12 H 18 O 4 , which was confirmed by high-resolution electron-impact mass spectrometry. An analysis of PMR and 13 C NMR spectra, 1 H-1 H COSY, HSQC, and HMBC spectra for 4 (Table 4) and a comparison of them with the data for 3 indicated that 4 had the same spiro [4,5]decene skeleton. The differences in chemical shifts of protons in the (S)-and (R)-MTPA esters (4a and 4b) proved the absolute configuration of C-10 as S. The 1D NOE-correlations of HC-10 in 4b with protons of the C-8 methyl and with HC-6D confirmed that these protons and H 3 C-1ccc were axial and that C-8 had the R-configuration in 4.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Compound 4 had molecular formula C 12 H 18 O 4 , which was confirmed by high-resolution electron-impact mass spectrometry. An analysis of PMR and 13 C NMR spectra, 1 H-1 H COSY, HSQC, and HMBC spectra for 4 (Table 4) and a comparison of them with the data for 3 indicated that 4 had the same spiro [4,5]decene skeleton. The differences in chemical shifts of protons in the (S)-and (R)-MTPA esters (4a and 4b) proved the absolute configuration of C-10 as S. The 1D NOE-correlations of HC-10 in 4b with protons of the C-8 methyl and with HC-6D confirmed that these protons and H 3 C-1ccc were axial and that C-8 had the R-configuration in 4.…”
mentioning
confidence: 96%
“…2). Thus, 3 was (5S,8R,10S)-8,10-dihydroxy-2,2,8-trimethyl-1-oxaspiro [4,5]dec-3-en-7-one. Compound 4 had molecular formula C 12 H 18 O 4 , which was confirmed by high-resolution electron-impact mass spectrometry.…”
mentioning
confidence: 98%
See 3 more Smart Citations